Security and Insecurity in Salvador: What do Public Security Indicators Reveal? - Tânia Benevides (2021)
This article evaluated the public security indicators, seeking to understand what the data from Intentional Lethal Violent Crimes (CVLI) and Violent Crimes against Heritage (CVP) reveal, compiled by the State of Bahia Public Security Secretariat (SSP-BA), between the years 2017 and 2019. The study starts from the following research question: what do the public security indicators CVLI and CVP reveal about the city of Salvador? The general objective of this article is to characterize security or insecurity in the city of Salvador from these two indicators. To this end, a descriptive research with a qualitative approach was carried out, based on the field research of the Quality Project of the Urban Environment of Salvador (QUALISalvador) in 2019, and based on the documentary research circumscribed by the data report on the crime records provided by the SSP -BA in the aforementioned period. An analysis of secondary data did not seek generalizations, focusing on the analysis of the city of Salvador, respecting local specificities and took place through the following steps: reading of the collected data; categorization of data into smaller units - between the years 2017 to 2019 and by grouping the CVP and CVLI indicators; analysis through comparison for refinement - with the definition of categories and identification of patterns; in addition to the confrontation between the data collected in the document and as analytical categories of the theoretical framework. It was found that the number of homicides in Salvador is very large, which corroborates the secondary data published by the 2019 Atlas of Violence, which revealed Salvador as the fifth most violent capital in Brazil.